Bringing the imperial back in: Reconsidering governance in the late Ottoman Empire, 1839–1923 (Part I). Issue 8 (20th July 2021) - Kuehn, Thomas
Abstract: This is the first of two connected articles that survey recent trends in the historical scholarship of Ottoman imperial governance from the beginning of the Tanzimat state building efforts in the 1830s to the end of empire in the early 1920s. In both articles, I examine how historians have answered the question of what was imperial about the ways in which the Ottoman Empire was governed during this period. Throughout this two‐part series I argue that an approach that pays attention to the capacity to govern, as Jane Burbank and Frederick Cooper put it, "different people differently" through a broad repertoire of rule, balancing this politics of difference with the politics of incorporation, is more conducive to bringing out the complexities of late Ottoman governance than teleological assumptions that consider the empire during this period on a linear path toward the nation state. Part I begins with a brief discussion of different ways in which historians have conceptualized imperial governance in the Ottoman context. I will then demonstrate that scholarship on the empire's peripheries in Transjordan, Mount Lebanon, Yemen, and Albania was instrumental in reframing the study of late Ottoman governance by taking its imperial dimensions seriously.